2021
DOI: 10.26442/20795696.2021.6.201286
|View full text |Cite
|
Sign up to set email alerts
|

Results of a clinical study of the drug efficacy and safety for intravesical administration based on bacteriophages in therapy in patients with chronic recurrent cystitis

Abstract: Background. Urinary tract infections remain one of the urgent problems in the aspect of qualified medical care. The causative agents of nosocomial infections are becoming more and more resistant to the drugs used, while the rate of new drugs synthesis is lower than the rate of development of antibiotic resistance. Routine and empirical prevention of recurrent urinary tract infections is often ineffective. Aim. To study the efficacy and safety of intravesical application of the drug based on bacteriophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“… 31 , 32 In one study, bladder instillation was compared with intrarectal or both routes of administration concurrently. 33 Phages were also given topically, via cystostomy, and intravesically with or without vaginal administration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 31 , 32 In one study, bladder instillation was compared with intrarectal or both routes of administration concurrently. 33 Phages were also given topically, via cystostomy, and intravesically with or without vaginal administration.…”
Section: Resultsmentioning
confidence: 99%
“…This work has now progressed to a large phase 2/3 trial for phage therapy in acute UTI. The Zaitsev et al RCT 33 reported significant efficacy with bladder instillation of phage in women with recurrent UTI.…”
Section: Discussionmentioning
confidence: 99%